RESTRICTIONS ON THE VOTING RIGHTS OF FORMER CORRUPTOR CONSTITUTIONS - Maria Virginia Usfunan (Khairun Law Journal, 2023)
One form of popular sovereignty is through general elections. This is evidenced by the provisions of Article 1 point 1 of Law Number 7 of 2017 concerning General Elections (Election Law) which stipulates "General Elections, hereinafter referred to as Elections, are a means of people's sovereignty to elect members of the People's Legislative Assembly, members of the Regional Representatives Council, President, and Vice President, to elect members of the Regional People's Legislative Council, which is carried out directly, publicly, freely, confidentially, honestly and fairly within the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution of the Republic of Indonesia". General elections that are held directly, publicly, freely, confidentially, honestly and fairly are expected to truly protect human rights in accordance with the guarantee of legal certainty and justice. However, the General Elections Commission has regulations that prohibit every corrupt ex-convict from becoming a candidate for member of the People's Representative Council of the Republic of Indonesia/Regional People's Representative Council and Regional Representative Council (DPR-RI/DPRD and DPD). This study uses a normative research method with a statutory approach (statue approach) and a conceptual approach (conceptual statue).Sources of legal materials are obtained from primary legal materials, secondary legal materials, tertiary legal materials. The technique for collecting legal materials in legal research is carried out through a card system. The analysis technique used in this research is descriptive analytic analysis technique. In addition, it also uses evaluation techniques which are carried out by providing an assessment to find out whether a view, proposition, statement of norms, and decisions contained in legal materials is appropriate or not, and the last is argumentation technique. This argumentation technique cannot be separated from evaluation techniques. because the assessment must be based on reasons that are in accordance with legal logic..